Etika Budaya Mengantre Dalam Kehidupan Sehari-Hari - Dede Siti Patimah; Ester Tania Marbun; Reffa Fakhri Dwitama; Azzahra, Vianca Nayla (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Recently, many societies have begun to forget about the culture of antre. It has been seen that most Indonesians are unwilling to join and many are cutting off other people’s ranks. This is because of the retreat of ethical culture that has begun not to be taught anymore in moral and character education. The ethics of this culture is centered on the teaching not on what the punishment is. The ethics of entering culture must be taught to society from an early age, starting with the child being given the right information and required by the child to be able to practice the right behavior. Besides, children should be taught how to build good relationships like how to appreciate others or even older people. The purpose of this research is to learn and understand how an ethical culture of entrance is carried out in Indonesia. The type of research used in this research is normative ethics with data collection techniques is documentation and library research with methods of qualitative descriptive approach. The results of this study show that the more advanced the age, the more the ethics of the society, which at this time the abduction is happening among today’s society. Therefore it is necessary to understand to the public about ethics in entering because the habit of not entering is often a major problem in society. The expression that "Budayakan Antri" is often heard is only a discourse, without any practice or action that becomes the habit of the people on a day-to-day basis. Because of the lack of public concern to create discipline that starts from the people themselves.